Myogenic conversion of cultured cells by azapyrimidines - Constantinides, P. G; Constantinides, P. G (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc. (medical biochemistry))- University of Stellenbosch, 1977.